Digital storytelling : impact of environmental factors on augmented reality - Elísa Eik Guðjónsdóttir 1996-; Emil Örn Kristjánsson 1995-; Ríkharður Friðgeirsson 1992- (2022)
A person's interest in the historical heritage has always been great and will probably always be. However, times are changing, and rapid technological development has revealed new ways to share stories. To date, the preservation and manifestation of the historical heritage have evolved from oral sources into written stories that have evolved into films and series. It can be stated that the time has come for future developments in storytelling in the form of Augmented Reality. It allows users to experience virtual objects in conjunction with a real-world environment where technology projects either visual material, audio recordings, or other information into the real world in an interactive way, to improve the user experience. The study aims to examine the impact of environmental factors on Augmented Reality (AR) experiences in Iceland and obtain some clues as to which factors have the greatest impact on the experiences. The study seeks to answer whether it is possible to create AR experiences in Iceland’s most historical places, where the risk factors are many and variable. These include ever-changing climates and lighting conditions. Emphasis will be placed on examining the effects of different lighting conditions, variable results between smartphones, and length measurements. The project spanned a 15 week period and included work in three major aspects. First, the subject of the research was examined and what AR technology has to offer. Subsequently, an AR testing platform was developed that measures accuracy and distance of AR tests. It was used to gather tangible results of the researchers tests and thus significant results of the research. The third and main subject of the project was the testing of the various prototypes where the AR Testing Platform was used for data collection. Each prototype was made to examine certain environmental factors that could lead to interesting and important results. The results of the study have shown that it is possible to make an Augmented Reality experience in Iceland, ...